Flavor‐Enhancing Properties of Mushrooms in Meat‐Based Dishes in Which Sodium Has Been Reduced and Meat Has Been Partially Substituted with Mushrooms. Issue 9 (14th August 2014) - Myrdal Miller, A.; Mills, K.; Wong, T.; Drescher, G.; Lee, S.M.; Sirimuangmoon, C.; Schaefer, S.; Langstaff, S.; Minor, B.; Guinard, J.‐X
Abstract The effects of beef substitution with crimini or white mushrooms (Agaricus bisporus) on the flavor profiles of carne asada and beef taco blends were measured with a descriptive analysis panel. Sensory mitigation of sodium reduction through the incorporation of mushrooms was also investigated in the taco blends. The substitution of beef with mushrooms in the carne asada did not alter the overall flavor strength of the dish, but the incorporation of 50% or 80% ground mushroom in the beef taco blend did enhance its overall flavor as well as mushroom, veggie, onion, garlic and earthy flavors, and umami and sweet tastes. Overall flavor intensity of the 25% reduced‐salt version of the 80% mushroom taco blend matched that of the full‐salt versions of the 100% and 50% beef formulations, thus indicating that the substitution of 80% of the meat with mushrooms did mitigate the 25% sodium reduction in terms of the overall flavor impact of the dish, even if it did not quite compensate for the reduction in salty taste. This proof‐of‐concept study for the Healthy Flavors Research Initiative indicates that because of their flavor‐enhancing umami principles, mushrooms can be used as a healthy substitute for meat and a mitigating agent for sodium reduction in meat‐based dishes without loss of overall flavor.